Penerapan Kombinasi Model Panutan Untuk Meningkatkan Keterampilan Berpikir Kritis Siswa Kelas Iv Pada Muatan Matematika - Try Novia Putri; Akhmad Riandy Agusta (CV. ITTC INDONESIA, 2024)
The low level of student activity and critical thinking skills in learning mathematics is a problem in this study. The causative factors are conventional learning methods, lack of application of critical thinking development, learning that is not student-centered, and limited learning media. This study aims to analyze the improvement of learning activities, critical thinking skills, and student learning outcomes through the application of the PANUTAN model. The research method used was Classroom Action Research (PTK) with three meetings. The subjects of this study were fourth grade students of SDN Tamban Muara 2 Barito Kuala Regency totaling 17 people. Qualitative data were obtained through observations of teacher activities, student activities, and students' critical thinking skills, while quantitative data were obtained through group and individual written tests for student learning outcomes. Data analysis was carried out using descriptive analysis techniques, cross tabulation, tables, graphs, and percentage interpretation. The results showed an increase in teacher activity from 38% to 100%. Student activity also increased significantly from 29% to 94%. Students' critical thinking skills increased from 23% to 94%. This had an impact on improving students' cognitive, affective, and psychomotor learning outcomes classically from 65% to 100%. In the conclusion of this study, the use of the PANUTAN model combination can improve teacher activity, student activity, critical thinking skills, and student learning outcomes